Enhancing Early Reading Skills through Integrated VAKT and Contextual Learning: A Classroom Action Research with First-Grade Students with Learning Difficulties - Ristyaningsih, Ristyaningsih; Pujaningsih, Pujaningsih (Journal of Innovation and Research in Primary Education, 2025)
Early reading proficiency represents a fundamental prerequisite for academic success, yet approximately 30% of kindergarten students demonstrate resistance to conventional reading instruction. Students with learning difficulties face particular challenges in mastering foundational reading skills, necessitating specialized intervention approaches. This study investigated the effectiveness of integrating Visual, Auditory, Kinesthetic, and Tactile (VAKT) methodology with contextual learning principles for improving beginning reading skills among first-grade students with learning difficulties. A qualitative classroom action research design following the Kemmis and McTaggart model was employed with five first-grade students (aged 7.1-8.7 years) experiencing difficulties reading CVDCC pattern words. The intervention integrated systematic VAKT activities with contextual learning elements across two cycles, each consisting of three intervention sessions and one assessment session. Data collection utilized reading performance assessments and observational protocols measuring student participation and teacher implementation fidelity. Substantial improvements were observed across both intervention cycles. Pre-intervention mean performance of 24% increased to 68% following Cycle I and reached 96% after Cycle II, with all participants exceeding the 80% success criterion. Students demonstrated enhanced engagement and sustained attention when interventions incorporated optimal scheduling and multisensory activities. Three participants achieved perfect scores (100%) while two reached 90% proficiency levels. The integrated VAKT-contextual approach effectively addressed reading challenges by compensating for individual processing weaknesses through multiple learning modalities while connecting abstract concepts to meaningful, familiar contexts. The intervention provides a structured, implementable framework for inclusive classroom practices supporting diverse learners with beginning reading difficulties.